2020
DOI: 10.1111/jar.12801
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐mediated therapy to reduce worrying in persons with visual and intellectual disabilities

Abstract: Increasing numbers of studies have investigated social robotics in mental health care, as described in recent reviews (Rabbitt, Kazdin, & Scassellati, 2015; Robinson, Cottier, & Kavanagh, 2019). To date, applications of robots in mental health care have been limited to the contexts of children's health, autism spectrum disorder and older adults with dementia. In such settings, robots are often used for stress reduction (Crossman, Kazdin, & Kitt, 2018; Dang & Tapus, 2013), to promote positive engagement in pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…ref. [90]), it will be valuable for future research to consider additional aspects of interactions with social robots, including the form of broadcasting and privacy matters.…”
Section: Overall Disclosure Differs By Agent Not Topicmentioning
confidence: 99%
“…ref. [90]), it will be valuable for future research to consider additional aspects of interactions with social robots, including the form of broadcasting and privacy matters.…”
Section: Overall Disclosure Differs By Agent Not Topicmentioning
confidence: 99%
“…For having more effective stress coping support, we need to consider a long-term interaction. For example, a past study reported the effectiveness of robot-mediated therapeutic intervention for people with visual and intellectual disabilities that was done for more than one month [38]. Designing conversational contents and memorization functions considering the changes of users' concerns and their self-schemas would be needed in long-term interaction.…”
Section: A Implicationsmentioning
confidence: 99%
“…It can be a bridge for interaction with autistic children, improving their social skills (HAN et al, 2018), assist in treatment of children with cancer (Ranjkar et al, 2019), contribute with wrist (English & Howard, 2017a) and upper limb (Kikuchi et al, 2018) rehabilitation. Furthermore, it can contribute to therapeutic interventions in order to support people with visual and intellectual disabilities (Wingerden et al, 2020).…”
Section: Introductionmentioning
confidence: 99%